The Antinomies of Academic Freedom: Reason, Trans Rights, and Constituent Power - Popowich, Sam (Canadian Journal of Academic Librarianship / Revue canadienne de bibliothéconomie universitaire, 2020)
This article challenges the dominant conception of academic freedom by critiquing the liberal philosophy that underpins it. The article uses recent issues around trans rights in both public and academic librarianship to show how the dominant liberal conception of academic freedom supports transphobia. It then uses Antonio Negri's theory of consituent power to offer an alternative perspective on academic freedom and how this alternative conception might better support trans rights in universities and libraries.